Analisis Wacana Kritis Model Van Dijk Terhadap Berita “Ma Wara’a al-Hill fi al-Munadharat al-Intikhobiyyah fi Indunisiya” dari Laman Indonesiaalyoum.com - Ishak, Dina Mustika; Kholisin, Kholisin (Prosiding Konferensi Nasional Bahasa Arab, 2024)
The debate over the election of presidential and vice presidential candidates is currently a hot topic of discussion. This social phenomenon has attracted the attention of all people in Indonesia, especially since the election debate was characterized by the use of tricks by each pair of candidates. This research aims to analyze text structure, social cognition, and social context in online news entitled